Response of viewers and non-viewers towards the gay theme of GMA's my husband's lover - Castillon, Eurika Jessa; Grantos, Jilleah; Sandig, Cor Mariez (2014.)
GMA?s My Husband?s Lover (MHL) was considered a breakthrough in Philippine television for being the first TV series that presented diverse and realistic portrayal of homosexuals. The success of the TV drama in a predominantly Catholic country has driven the researchers to conduct a study on the response of the male and female population towards this portrayal. A survey questionnaire was designed to determine the response of viewing and non-viewing population on the gay theme of MHL; thereafter, further identifying the factors that influence the response of the survey population. Research results showed that the viewers of My Husband?s Lover had a higher positive response (48%), compared to that of the non-viewing population (42%). It was further discovered that MHL viewers are more accepting of the show?s gay theme than the non-viewers. Several factors that evidently influence the heterosexuals? responses were identified; namely, religious and moral beliefs, prejudiced societal influences, family upbringing, collegiate or familial relationship with gays and the mediality of television.
Thesis -- Bachelor of Arts in Communication and Media Studies. University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Homosexual Theme; Television (TV) Drama; Viewership